Systemic Biomarkers Predictive of Anatomical and Functional Outcomes of Macular Edema Secondary to Retinal Vein Occlusion Following a Single Injection of Intravitreal Bevacizumab - Tagare, Shivraj; Sindal, Manavi D (Nepalese Journal of Ophthalmology, 2024)
Introduction: Macular edema (ME) secondary to retinal vein occlusion (RVO) is a leading cause for visual impairment. Objective: To identify the systemic biomarkers that influence the anatomical and functional outcomes of a single injection of intravitreal bevacizumab (IVB) for RVO related macular edema ME. Methodology: A prospective interventional study was conducted on patients with treatment naïve RVO induced ME, from November 2019 to April 2021 after ethical approval. All participants underwent a complete systemic evaluation consisting of blood pressure measurement, blood sugar, glycosylated hemoglobin, hemoglobin, total and differential cell counts, lipid profile and renal function tests at baseline. IVB was administered for RVO induced ME. Anatomical outcome was measured as change in macular thickness from baseline to one month after treatment on optical coherence tomography and functional outcomes were improvement in visual acuity. Result: Median best corrected visual acuity improved from 0.56±0.39 to 0.4±0.4 LogMAR (p <0.001) with significant reduction in mean central retina thickness (CRT) from 609.9±216.5 μ to 337.6±168.2 μ (p <0.001) at one month. On evaluating systemic parameters, longer duration of hypertension (r = -0.2795, p = 0.037), and those with higher eosinophil count (r = -0.2595, p = 0.025) were less likely to have a reduction in CRT. Higher HDL levels (r = 0.2505, p = 0.031) and better RBC counts (r = 0.2732, p = 0.016) were more likely to be predictive of a better reduction of CRT. Conclusion: Patients with RVO related ME can experience visual improvement and reduction in edema at initiation of treatment. Systemic biomarkers correlating to those for cardiovascular morbidity influence outcomes of ME. Optimum management of these modifiable systemic biomarkers can enhance treatment outcomes.